Secondary acute angle-closure attack: Diagnosis and management - Sakaorat Petchyim (2019)
© 2018, Faculty of Medicine Siriraj Hospital, Mahidol University. Patients may come with acute angle-closure attack that mimics primary disease, but actually there was a hidden cause. Mostly, fellow eye with wide open angle might be a clue for secondary cause. However, an area with high prevalence of narrow angle makes it harder to notice while fellow eye has narrow angle too. The most important thing in order to approach acute angle-closure attack is to know a possible underlying cause that should be looked for. This article will simplify various pathologies that could result in secondary acute angle-closure attack. Clinical presentation, special investigation and treatment were all summarized.